Edukasi Teknologi Vertikultur Tanaman Sayuran pada Lahan Pekarangan di Kelurahan Pai Kota Makassar - Suraedah Alimuddin; A. St. Fatmawati (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2026)
This Community Service Program (PKM) was conducted in collaboration with Majelis Taklim Nurhidayah, located in an urban area with relatively limited home yard space. Verticulture is an innovative cultivation system that utilizes vertical space, making it suitable for application in narrow urban areas. However, the partners’ knowledge and skills in vegetable cultivation using the verticulture system were still limited. The aim of this PKM activity was to improve the partners’ knowledge and skills in applying verticulture technology for vegetable cultivation in home yards. The methods included counseling, training/demonstration, mentoring, and evaluation and monitoring to assess the partners’ progress. The results showed that the program successfully enhanced the partners’ understanding and technical ability in verticulture-based vegetable cultivation, as well as their creativity in reusing plastic bottles and cups as planting containers. The partners expressed high appreciation for the PKM program, as reflected in their high level of satisfaction and their commitment to continue verticulture cultivation independently at home. The program has received full support to ensure its sustainability, especially in promoting vegetable cultivation through verticulture as an effort to enhance household food security.